Alumni network: hati ke hati bersama alumni APB - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
A meeting with alumni from APB was held on 1st October 2022, at UiTM Hotel Shah Alam. A total of 27 APB alumni and 23 staff from APB took part in this gettogether. The meet up aimed to offer opportunity to the alumni to share their feedback and opinion with the APB management. The discussion highlighted a few aspects which were (1) cooperation between APB and alumni, (2) practical training or internship opportunities for APB students, (3) proposed activities to be conducted with APB and alumni involvement, (4) APB's contribution to alumni, and (5) alumni's contribution to Tabung Amanah APB. The Dean welcomes the alumni to establish collaborative relationship with APB to further strengthen the relationship between the faculty and the alumni.